Optimizing Digitalization of Islamic School Administration with Cloud Storage: A Socio-Economic Review in The Perspective of Social Studies Education - Khairani, Najwa Azka; Hadi, Syamsul (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2025)
The digitalization of school administration using cloud storage has emerged as an innovative solution to enhance data management efficiency in Islamic schools. This study aims to analyze the social and economic impacts of digitalized administration while identifying key challenges in its implementation. A mixed methods approach was employed, integrating quantitative surveys and qualitative interviews with school administrators and staff in Islamic schools in Bogor. In this study, ethical aspects were strictly observed. Respondents were explained the purpose of the study and given the option to participate voluntarily. Informed consent was obtained in writing prior to data collection, and data confidentiality was maintained. Findings reveal that most Islamic schools are still transitioning to digital systems, while only a small number have fully implemented digitalization. Google Drive is the preferred platform, highlighting its accessibility and collaboration features. From a social perspective, digitalized administration improves work efficiency, communication, and reduces manual workload. However, challenges such as limited internet access, data security concerns, and lack of staff training remain significant obstacles. Economically, digitalization contributes to operational cost savings, particularly in reducing paper and stationery expenses. However, cost savings are perceived as moderate, suggesting that long-term financial benefits require further optimization. To address these challenges, Islamic schools must invest in internet infrastructure, enhance data security, and allocate budgets for staff training to ensure effective implementation. With the right strategies, cloud-based digital administration holds great potential to improve operational efficiency, management transparency, and educational service quality in Islamic schools.